2020
DOI: 10.1200/jco.19.03024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Asparaginase Discontinuation on Outcome in Childhood Acute Lymphoblastic Leukemia: A Report From the Children’s Oncology Group

Abstract: PURPOSE Asparaginase (ASNase) is an important component of acute lymphoblastic leukemia (ALL) treatment, but is often discontinued because of toxicity. Erwinia chrysanthemi ASNase ( Erwinia) substitution was approved in 2011 for allergic reactions. Erwinia has, however, been intermittently unavailable because of drug supply issues. The impact of Erwinia substitution or complete ASNase discontinuation is unknown. METHODS Patients aged 1-30.99 years in frontline Children’s Oncology Group trials for B-cell acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(174 citation statements)
references
References 26 publications
7
166
1
Order By: Relevance
“…Discontinuation of planned asparaginase doses is associated with worse prognosis in high-risk patients. 107 In cases of allergy to pegaspargase or native E. coli asparaginase, Erwinia asparaginase (Erwinase) is considered an acceptable alternative. However, Erwinase is more expensive, is intermittently unavailable, and requires frequent administration because of its short half-life.…”
Section: Remission-induction Therapymentioning
confidence: 99%
“…Discontinuation of planned asparaginase doses is associated with worse prognosis in high-risk patients. 107 In cases of allergy to pegaspargase or native E. coli asparaginase, Erwinia asparaginase (Erwinase) is considered an acceptable alternative. However, Erwinase is more expensive, is intermittently unavailable, and requires frequent administration because of its short half-life.…”
Section: Remission-induction Therapymentioning
confidence: 99%
“…This was also the case for patients with hypersensitivity reactions who were shifted to formulations with a shorter half-life, for example, Erwinia asparaginase. 4 An earlier Dana-Farber Cancer Institute (DFCI) ALL Consortium study (91-01) showed that patients who tolerated 25 or fewer weeks of asparaginase had a significantly worse outcome than those who received at least 26 weeks of asparaginase. 3 Noteworthy, 30 weeks of PEG asparaginase exposure were associated to a similar EFS whether asparaginase was administered at 2 or 6 weeks intervals.…”
Section: Asparaginasementioning
confidence: 99%
“…This has led to an unmodified outcome in two large COG studies devoted to National Cancer Institute (NCI) standard risk B-ALL (AALL0331) and NCI high risk B-ALL (AALL0232). 4 Premedication could lead to a further reduction of IRRs (see the section on Premedication below). 21 Also it has to be recognised that regular shortages of Erwinia asparaginase are occurring worldwide.…”
Section: Asparaginasementioning
confidence: 99%
See 2 more Smart Citations